8 - Book Reviews: Patrick Obeng-Fosu, Industrial Relations in Ghana: The Law and Practice , The Ghana Universities Press, Accra, Ghana, 1991, pp.152: par Kwamina Panford - Kwamina Panford, (Africa Development, 1993)
Abstract